A Review for Aqueous Electrochemical Supercapacitors - Zhao, Cuimei; Zheng, Weitao (Frontiers in Energy Research, 2015)
Electrochemical capacitor is the most promising energy-storage device that can meet the demands of high-power supply and long cycle life; however, low-energy density and high-fabrication cost limit its further development. Researchers have paid more attention to the development of electrode material in the past, and very few people attach importance to the research of the electrolyte, especially the redox electrolyte, which is important for improving specific capacitance greatly. This paper presents a review of the research in not only electrode material but also redox aqueous electrolyte and together with an important part of supercapacitor device. The advantages and disadvantages for different electrode material and electrolyte are discussed. And the new trends in supercapacitor development are also summarized.